Coaching Model of Science Teacher Professionalism Through MGMP Teaching Clinic Management - Ngurah Ayu Nyoman Murniati (Bandar Lampung University (UBL), 2014)
Efforts to improve the quality of education through teacher development needs serious attention. One of the flagship projects implemented through professional organizations MGMP empowerment. MGMP can be developed as a forum for the professional development of teachers. Facts on the ground indicate that the performance of MGMP still low. It is a challenge science teachers professional development. Formulation of the research problem is how the model of coaching junior high science teacher professionalism in management MGMP Teaching Clinic? The purpose of research described Teaching Clinic MGMP management model as a model of professionalism coaching junior high school science teacher. Benefits of the research as materials development science education human resource management (MSDMP). The model developed can be used as study design, organization, coaching, evaluating performance and professionalism of science teachers. The study design is a Research and Development (R & D) to develop management models MGMP Science Teaching Clinic SMP Semarang. The products produced in this study is the management model and the Guidelines for Teaching Clinic MGMP. Validation results showed the model can be used as a junior high science teacher professional development. The effectiveness of the model shown in performance enhancement science teacher before and after participating in the Cluster Clinical Didactic methodical. This means that the performance of science teachers through the Teaching Clinic is better than before. Conclusions showed that MGMP empowerment through Teaching Clinic to improve service quality in building and developing the junior high science teacher professionalism. Teaching Clinic MGMP serves as a follow-up professionally assistance given to teachers who have problems. Recommended science teacher, MGMP, Teaching Management Clinic at the Department of Education and related agencies as a model of training and professional development of teachers through MGMP.